2009
DOI: 10.1007/s12272-009-2218-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol induces apoptosis via activation of both mitochondrial and death receptor pathways in A375-S2 cells

Abstract: Magnolol inhibited proliferation of human malignant melanoma A375-S2 cells. The drug induced oligonucleosomal fragmentation of DNA in A375-S2 cells and increased caspase-3, 8, 9 activities followed by the degradation of caspase-3 substrates, inhibitor of caspase dependent DNase (ICAD) and poly-(ADP-ribose) polymerase (PARP). Pan-caspase inhibitor (z-VADfmk), caspase-3 inhibitor (z-DEVD-fmk), capase-8 inhibitor (z-IETD-fmk), caspase-9 inhibitor (z-LEHD-fmk) and caspase-10 inhibitor (z-AEVD-fmk) inhibited magnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…1C). These results suggest that Magnolol can act as growth inhibitor of gastric adenocarcinoma SGC-7901 cells in a similar fashion as described in previous studies dealing with various other types of cancer cells including melanoma cells (21), colon cancer cells (24,25), prostrate cancer cells (26,27), human glioblastoma cancer cells (28,29), liver cancer cells (32), lung cancer cells (30,31), leukemic cells (14), thyroid carcinoma cells (33), and human urinary bladder cancer 5637 cells (35). …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…1C). These results suggest that Magnolol can act as growth inhibitor of gastric adenocarcinoma SGC-7901 cells in a similar fashion as described in previous studies dealing with various other types of cancer cells including melanoma cells (21), colon cancer cells (24,25), prostrate cancer cells (26,27), human glioblastoma cancer cells (28,29), liver cancer cells (32), lung cancer cells (30,31), leukemic cells (14), thyroid carcinoma cells (33), and human urinary bladder cancer 5637 cells (35). …”
Section: Resultssupporting
confidence: 85%
“…Apoptosis is one of the modes of cell death and induction of apoptosis is the key characteristic of anticancer drugs as it plays an imperative role in the elimination of damaged cells and the maintenance of homeostasis and many of the natural chemopreventive agents, including Magnolol, exert their effect via induction of apoptosis in cancer cells (21,49,50). To elucidate the effect of Magnolol on induction of apoptosis in SGC-7901 cells, these cells were treated with Magnolol and incubated with PI, analysed by flow cytometry and resulted in the increase of subG1 phase which represents the apoptotic cell population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnolol induces apoptosis via activation of both mitochondrial and death receptor pathways in A375-S2 malignant melanoma cells [54]. Recent studies by Tanaka et al [55], have shown the preventive effects of magnolol on UV-induced photoaging by inhibiting the expression of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MAG also suppressed ERK1/2 kinase, MAPK, and the PI3K/AKT pathway in DMBA/TPA-induced skin cancer in female mice [155]. MAG inhibited cell proliferation in the human malignant melanoma A375-S2 cell line by increasing caspases-3, -8,-9 activities, augmenting the expression of anti-apoptotic mitochondrial protein Bcl-2 while decreasing the expression of pro-apoptotic protein Bax [147]. In vivo studies on different animal models of skin cancer demonstrated that MAG reduced tumor growth, induced apoptosis and arrested cell cycle at the G2/M phase (Table 1) [56,156,157].…”
Section: Effect Of Magnolol In Different Cancersmentioning
confidence: 99%